Analisis Penggunaan Antibiotik pada Pasien Covid -19 Di Ruang Isolasi Rumah Sakit X Tipe D Kabupaten Malang - Retno Juwita Sari; Rika Yulia; Fauna Herawati (LPPM Hang Tuah Pekanbaru, 2023)
COVID-19 cases by the end of 2019 have raised the number of respiratory tract infections; in addition, coinfection during COVID-19 pandemic is associated with disease severity, consequently,causes the number of deaths to surge. The use of antibiotics during the pandemic has evidently improved in a significant way, similar to the increased number of broad-spectrum prescriptions. This phenomenon potentially elevates the number of Antimicrobial Resistance (AMR); therefore, it is necessary to fortify supervision over the use of antibiotics during COVID-19 pandemic. Referring to this, the objective of the study is to evaluate the use of antibiotic during COVID-19 pandemic. This is an observational study conducted on adult subjects with confirmed COVID-19, with moderate to severe level of disease, whose data was collected retrospectively during the period of April 2020 – March 2021. The result confirmed 146 patients were treated as sample of the study, most of whomwere male (53.4%),and female was 46.6%. The highest age group was 56 – 65 years old by 28.8%. The increase in leukocyte level > 1.000 was 31.5%. 8 (eight) types of antibiotics were used in high frequency, such as, injection levofloxacin antibiotics (50%),while frequently used combination antibioticswere ceftriaxone and levofloxacin (5.5%). Based on quantitative analysis, the total value was 60,54 DDD/100 patient-days, and the value of antibiotic with the highest DDD was levofloxacin 26.51 DDD/100 patient-days. Additionally, the result of analysis on the quality of antibiotics using Gyssens flowchart suggested 36.3% of the given antibiotic were considered as rational (category 0) and 46.6% of the given antibiotics had no indication of usage (category V). Prospective research is needed regarding the use of antibiotics.